Real-time trajectory planning for ship-mounted rotary cranes considering continuous sea wave disturbances - Wu, Qiangying; Ouyang, Huimin; Xi, Huan (Nonlinear dynamics, 2023)
The increasing use of ship-mounted rotary cranes in marine trade has complicated operations, as the varying rope length increases the system’s underactuation. Additionally, these cranes are often subject to wave disturbances during load transportation. This paper proposes a trajectory planning method based on disturbance observer to address these challenges. To begin, coordinate transformations are used to couple continuous yaw and roll disturbances with the original state variables, creating new state variables. A disturbance observer is then used to observe heave disturbance while combining the designed sway suppression trajectory with the reference trajectory to achieve precise positioning of the load and suppress the swaying angle. The stability of the proposed method is demonstrated through the use of theoretical techniques such as Lyapunov, LaSalle’s invariance principle, and Barbalat’s lemma. Furthermore, the effectiveness of the proposed approach is confirmed through experiments conducted on a constructed experimental platform.